The Influence of Job Satisfaction, Work Discipline, Communication, and Work Environment on Employee Productivity at Setyo Mulyo Group - Bela Rahayu Rianingsih; Ratna Puji Astuti; Herwiek Diyah Lestari (Sean Institute, 2026)
Employee productivity is a key factor in determining organizational success and is influenced by various internal and workplace-related factors. This study aims to analyze the effects of job satisfaction, work discipline, communication, and the work environment on the work productivity of employees at Setyo Mulyo Group. This research employed a quantitative approach with a population of 71 employees of Setyo Mulyo Group. A total of 67 respondents were selected using the proportionate stratified random sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS Statistics 26. The results indicate that job satisfaction, work discipline, communication, and the work environment simultaneously and partially have a positive and significant effect on employee work productivity. These four independent variables explain 55.6% of the variation in employee productivity, while the remaining 44.4% is influenced by other factors outside the scope of this study. The findings suggest that improving job satisfaction, strengthening work discipline, promoting effective communication, and fostering a supportive work environment are essential to enhancing employee productivity. Therefore, organizations should implement sustainable human resource management policies that focus on employee well-being, organizational communication, compliance with work procedures, and the creation of a positive work environment. The findings are expected to serve as a reference for company management and future researchers in developing strategies to improve employee productivity.